The abatement of indigo carmine using active chlorine electrogenerated on ternary Sb2O5-doped Ti/RuO2-ZrO2 anodes in a filter-press FM01-LC reactor. (20th August 2015) - Palma-Goyes, R.E.; Vazquez-Arenas, J.; Torres-Palma, R.A.; Ostos, C.; Ferraro, F.; González, I.
Graphical abstract: Abstract: Dimensionally Stable Anodes (DSA) of Sb2 O5 -doped Ti/RuO2 -ZrO2 are prepared by the Pechini method to perform the degradation of indigo carmine (IC) under conditions similar to textile wastewater effluents. XRD results along with Rietveld refinement reveal that the co-deposited phases on the DSA exhibit a tetragonal crystal structure ( P4/mmm ) for RuO2 and monoclinic structure ( P2/m ) for ZrO2 . Degradation tests conducted in solutions containing 0.64 mM IC and 0.05 M NaCl using a filter-press reactor (FM01-LC) show that the degradation rate is faster and more efficient at 200 A m −2 with a flow rate of 5 L min −1, although the energy consumption is moderately higher. Under this condition, the pollutant is efficiently removed, and converted to aliphatic acid compounds of low molecular weight, as indicated by 90 % Chemical Oxygen Demand (COD), 22 % Total Organic Carbon (TOC) elimination, along with an Average Oxidation State (AOS) value equal to 3.0. The energy consumptions revealed that it is feasible to carry out the IC degradation under reasonable operating costs. Topological and Natural Bond Orbital (NBO) analyses are computed using density functional theory (DFT), and combined with experimental results to propose a reaction pathway for IC abatement.